2019
DOI: 10.1186/s12931-019-1023-0
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive high-frequency oscillatory ventilation as respiratory support in preterm infants: a meta-analysis of randomized controlled trials

Abstract: BackgroundNoninvasive high-frequency oscillatory ventilation (nHFOV), a relatively new modality, is gaining popularity despite scarce evidence. This meta-analysis was designed to evaluate the efficacy and safety of nHFOV as respiratory support in premature infants.MethodsWe searched MEDLINE, EMBASE, CINAHL, and Cochrane CENTRAL from inception of the database to January 2019. All published randomized controlled trials (RCTs) evaluating the effect of nHFOV therapy with nasal continuous positive airway pressure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 37 publications
2
55
0
Order By: Relevance
“…Ten studies were adjudged as having a high risk of bias due to issues in random sequence generation and allocation concealment. 30,32,33,39,40,[43][44][45]47,53 Eight studies had a low risk of bias 21,23,25,26,42,48,50,52 and fifteen studies had variable risk of bias. 22,24,[27][28][29]31,[34][35][36][37][38]41,46,49,51 Due to the nature of the intervention, blinding of the personnel and outcome assessor was not possible and hence all the trials scored a high risk of bias for the same.…”
Section: Risk Of Bias Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies were adjudged as having a high risk of bias due to issues in random sequence generation and allocation concealment. 30,32,33,39,40,[43][44][45]47,53 Eight studies had a low risk of bias 21,23,25,26,42,48,50,52 and fifteen studies had variable risk of bias. 22,24,[27][28][29]31,[34][35][36][37][38]41,46,49,51 Due to the nature of the intervention, blinding of the personnel and outcome assessor was not possible and hence all the trials scored a high risk of bias for the same.…”
Section: Risk Of Bias Of the Included Studiesmentioning
confidence: 99%
“…58 There were only two RCTs evaluating the efficacy of nHFOV with most of the evidence being contributed by the indirect fraction from other comparisons. 52,53 A recent meta-analysis had shown that nHFOV was better in preventing reintubation than CPAP. 59 Most of the trials included in this meta-analysis were small, and most had used nHFOV as a primary respiratory support.…”
Section: Excluding Trials With High Robmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Newer modalities of NRS strategies that have come into practice in neonatal medicine in the past two decades, include heated and humidified high flow cannula (HFNC), noninvasive positive pressure ventilation (NIPPV), bilevel CPAP (Bi-PAP) as well as nasal high-frequency oscillation ventilation (nHFOV). 4,5 Several systematic reviews compared different NRS strategies in pair-wise meta-analysis, however, only one network meta-analysis (NMA) evaluated different NRS strategies in preterm neonates with RDS. [6][7][8][9][10] The NMA by Isamaya et al 10 and mechanical ventilation [MV] following surfactant) along with CPAP and NIPPV.…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have provided evidence in support of the potential benefits. [ 9 , 10 ] A recent study confirms that LISA strategies decrease the risks of the composite outcome of BPD or death and of early nCPAP failure when compared to “intubation-surfactant-extubation” approaches, [ 9 ] and the latest European guideline recommends that LISA is the preferred mode of surfactant administration for spontaneously breathing babies on nCPAP for experienced clinicians. [ 3 ] Our meta-analysis found that in preterm infants, the use of nHFOV rather than nCPAP was beneficial in terms of improved CO 2 elimination and a reduced risk of intubation for mechanical ventilation.…”
Section: Discussionmentioning
confidence: 98%